2017
DOI: 10.7567/jjap.56.061002
|View full text |Cite
|
Sign up to set email alerts
|

Uneven AlGaN multiple quantum well for deep-ultraviolet LEDs grown on macrosteps and impact on electroluminescence spectral output

Abstract: AlGaN-based LEDs (λ < 300 nm) fabricated on n-AlGaN templates with a threading dislocation density larger than 5 × 108/cm2, which were grown on (0001) sapphire with a 1.0° miscut relative to the m-plane, showed external quantum efficiencies (EQEs) of 3.5, 3.9, 6.1, and 6.0% at 266, 271, 283, and 298 nm, respectively. These EQE values reveal significantly high internal quantum efficiencies (IQEs). This performance was obtained using an uneven multiple quantum well (MQW) grown on the AlGaN template with macroste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
92
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 40 publications
3
92
0
Order By: Relevance
“…However, the angle dependence of the optical properties is an interesting subject for future studies. It has been reported that Al x Ga 1− x N‐based UV LED on vicinal sapphire (0001) surfaces show high EQEs . The present study suggests that the high EQE originates due to the suppression of nonradiative recombination processes in the QWs grown on macrosteps.…”
supporting
confidence: 52%
“…However, the angle dependence of the optical properties is an interesting subject for future studies. It has been reported that Al x Ga 1− x N‐based UV LED on vicinal sapphire (0001) surfaces show high EQEs . The present study suggests that the high EQE originates due to the suppression of nonradiative recombination processes in the QWs grown on macrosteps.…”
supporting
confidence: 52%
“…The near‐surface region of the AlN template, the homoepitaxial AlN, the AlN/GaN SL, and the bottom of the Al 0.75 Ga 0.25 N buffer layer are visible. This ADF STEM image was obtained in the [11–20] AlN viewing direction and shows all dislocation types formed in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Exemplary cross‐sectional images of lower part of UVB‐LED structure on AlN template with TDD of (4 ± 0.2) × 10 9 cm −2 : a) ADF STEM showing formation of horizontal dislocation lines in AlN/GaN superlattice and strong TD inclination in subsequently grown AlGaN (viewed in [11‐20]AlN projection). b,c) Dark‐field diffraction contrast images of the same specimen area visualizing different types of defects (white arrows indicate the same specimen positions).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AlGaN‐based deep‐ultraviolet (DUV) ( λ < 300 nm) LEDs are expected to be useful for applications such as sterilization, deodorization, and UV curing. The high external quantum efficiencies (EQEs) of 6.1 and 6.0% at 283 and 291 nm without encapsulation and with thick p‐GaN (0.5 μm) show that internal quantum efficiency (IQE) is greater than 60% with a forward voltage ( V f ) of less than 6 V, meaning that bare die's performance has reached the level of practical application. A trial encapsulation showed EQE of 12% and a wall‐plug efficiency (WPE) of 5.5% with V f of 8.4 V at 278 nm using a transparent p‐cladding layer and p‐reflective electrode.…”
Section: Introductionmentioning
confidence: 99%